2011
DOI: 10.1007/s00284-011-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Murine Model for Investigation of Pathogenesis of Sudden Infant Death Syndrome

Abstract: Several studies have indicated a possible causative role of toxigenic bacteria in sudden infant death syndrome (SIDS). This study examined the effect of toxigenic E. coli on pregnant and infant mice to determine if these animals could be used as a model for SIDS pathogenesis. Strains of E. coli from the intestinal contents of infants who have died of SIDS or other causes and from the faeces of healthy infants were collected over a broad time scale. The isolates were tested for their ability to produce then kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…We have demonstrated that a SIDS-like condition can be established in a murine model (Bettelheim et al 2012). This and the significant work on interactions between cigarette smoke, virus infection and responses to bacterial toxins that has been carried out by Blood Siegfried and colleagues (2004) in a rat pup model as well as the earlier studies by Jakeman et al (1991) should provide important answers to the underlying mechanisms and the various parameters can be studied in detail.…”
Section: ) Evidence For Infection and Inflammation In Sids Pathogenesismentioning
confidence: 77%
“…We have demonstrated that a SIDS-like condition can be established in a murine model (Bettelheim et al 2012). This and the significant work on interactions between cigarette smoke, virus infection and responses to bacterial toxins that has been carried out by Blood Siegfried and colleagues (2004) in a rat pup model as well as the earlier studies by Jakeman et al (1991) should provide important answers to the underlying mechanisms and the various parameters can be studied in detail.…”
Section: ) Evidence For Infection and Inflammation In Sids Pathogenesismentioning
confidence: 77%
“…Dams exposed to the toxigenic strain had smaller litter sizes and some runting of the pups. Mortality was 18% for the SIDS E. coli strain compared to 9% for non-SIDS isolates ( 33 ) (Table 1 ). In a different mouse model, gamma herpes virus plus a non-lethal dose of endotoxin was responsible for a reduction of litter size and fetal loss ( 34 ) (Table 1 ).…”
Section: Synergy Of Infectious Agentsmentioning
confidence: 99%
“…Prone sleeping position plays a significant role in SIDS risk, not because of its effect on normal oxygen/carbon dioxide-exchange but rather on an increase in temperature. Elevated body temperature and increased toxin production by bacterial isolates in the nasal pharynx might be a contributing factor ( 33 , 63 , 64 ). Data suggest that prone position will exacerbate the consequences of a viral infection because it promotes an optimum temperature to increase the numbers and variety of bacterial species in upper respiratory secretions and stimulates bacterial toxin production ( 65 ).…”
Section: Respiration and Hyperthermiamentioning
confidence: 99%
“…In favor of a gut origin was the finding of non-Shiga toxin verotoxigenic Escherichia coli belonging to a restricted range of serogroups not seen in live matched control babies ( 15 ). In addition, these E. coli were capable of causing death in neonatal mouse pups ( 4 ). These studies led us to explore the role of the gut microbiome in SIDS, which gave us interesting preliminary findings ( 16 ).…”
Section: Introductionmentioning
confidence: 99%